From Coronal Holes to Pulsars and Back Again: Learning the Importance of Data - Wang, Y.-M. (Frontiers in Astronomy and Space Sciences, 2022)
Although wanting to become an astronomer from an early age, I ended up in solar physics purely by chance, after first working in high-energy astrophysics. I’ve never regretted switching from the pulsar to the solar magnetosphere, because solar physics has a great advantage over other areas of astrophysics—in the enormous amount of high-quality data available, much of it underutilized. I’ve often wondered why theoreticians and modelers don’t spent more time looking at these data (perhaps they feel that it is cheating, like taking a peek at the answers to a difficult homework assignment?). Conversely, I wonder why observers and data analysts aren’t more skeptical of the theoretical models—especially the fashionable ones.